Phytosynthesis of Silver Nanoparticles Using Perilla frutescens Leaf Extract: Characterization and Evaluation of Antibacterial, Antioxidant, and Anticancer Activities - Reddy NV (Dove Medical Press, 2021)
NV Reddy,1 Huizhen Li,1 Tianyu Hou,1 MS Bethu,2 Zhiqing Ren,1 Zhijun Zhang1 1School of Chemical Engineering and Technology, North University of China, Taiyuan, Shanxi Province, People’s Republic of China; 2Pharmacology and Toxicology Division, Indian Institute of Chemical Engineering and Technology, Hyderabad, Telangana State, IndiaCorrespondence: Zhijun ZhangSchool of Chemical Engineering and Technology, North University of China, Taiyuan, Shanxi Province 030051, People’s Republic of ChinaEmail sxzzj@163.comPurpose: The present study investigates the phytosynthesis of silver nanoparticles (AgNPs) using Perilla frutescens leaf extract, which acts as a reducing agent for the conversion of silver ions (Ag+) into AgNPs. P. frutescens leaf synthesized AgNPs (PF@AgNPs) were evaluated for biomedical properties including antibacterial, antioxidant and anticancer activities.Materials and Methods: PF@AgNPs were synthesized using P. frutescens leaf extract and silver nitrate solution. The morphology and physical properties of PF@AgNPs were studied by spectroscopic techniques including, UV-Vis, FTIR, TEM, XRD, DLS, and TGA. Antibacterial activity of PF@AgNPs was evaluated by disk diffusion assay. Antioxidant activity of PF@AgNPs was checked by 2.2-diphenyl-1-picrylhydrazyl (DPPH), and 2.2ʹ-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) free radical scavenging assays. Anticancer activity of PF@AgNPs was checked by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay. Cytotoxic effects of PF@AgNPs on most susceptible cancer cell lines were observed by phase contrast microscopy.Results: PF@AgNPs showed surface plasmon resonance peak at 461 nm. XRD pattern showed that the PF@AgNPs were face-centered cubic crystals with a mean size of 25.71 nm. TEM analysis revealed the different shapes (spherical, rhombic, triangle, and rod) of PF@AgNPs. Zeta potential value (− 25.83 mV) indicated that PF@AgNPs were long-term stable and not agglomerated. A low polydispersity index value (0.389) indicated the monodispersity of PF@AgNPs. TGA revealed the high thermal stability of PF@AgNPs. PF@AgNPs exhibited maximum inhibition against Escherichia coli, followed by Bacillus subtilis and Staphylococcus aureus. PF@AgNPs showed maximum inhibition of 68.02 and 62.93% against DPPH and ABTS-free radicals, respectively. PF@AgNPs showed significant anticancer activity against human colon cancer (COLO205) and prostate adenocarcinoma (LNCaP). PF@AgNPs exhibited apoptotic effects on LNCaP cells including cell shrinkage, membrane blebbing, chromatin condensation, fragmentation of nuclei, and formation of apoptotic bodies.Conclusion: The present study reports the successful synthesis of PF@AgNPs using P. frutescens leaf extract. The synthesized PF@AgNPs are FCC crystals, monodispersed, long-term stable, and non-agglomerated. The observed antibacterial, antioxidant, and anticancer activities demonstrate the potential biomedical applications of PF@AgNPs.Keywords: Perilla frutescens, silver nanoparticles, antibacterial activity, antioxidant activity, anticancer activity, LNCaP